1988
DOI: 10.1037/0021-9010.73.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary approaches to job design: A constructive replication with extensions.

Abstract: This study replicated Campion and Thayefs (1985) research, which drew from many disciplines (e.g., psychology, engineering, human factors, physiology) to demonstrate four approaches to job design and their corresponding outcomes: motivational approach with satisfaction outcomes, mechanistic approach with efficiency outcomes, biological approach with comfort outcomes, and perceptual/motor approach with reliability outcomes. This study extended the research in five ways. First, it used an expanded sample of 92 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
259
2
16

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(291 citation statements)
references
References 95 publications
(135 reference statements)
14
259
2
16
Order By: Relevance
“…As research expanded the range of work design outcomes studied, it became clear that designing work according to the principles of a motivational model (the predominant model in organizational psychology) involved several distinct trade-offs (Morgeson & Campion, 2002. In particular, although increasing motivational work design had the benefit of improved affective outcomes (i.e., job satisfaction), it also had the cost of increased training and compensation requirements, two important human resource outcomes (Campion, 1988;Campion & Thayer, 1985;Morgeson & Campion, 2003).…”
Section: Relationships To Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…As research expanded the range of work design outcomes studied, it became clear that designing work according to the principles of a motivational model (the predominant model in organizational psychology) involved several distinct trade-offs (Morgeson & Campion, 2002. In particular, although increasing motivational work design had the benefit of improved affective outcomes (i.e., job satisfaction), it also had the cost of increased training and compensation requirements, two important human resource outcomes (Campion, 1988;Campion & Thayer, 1985;Morgeson & Campion, 2003).…”
Section: Relationships To Outcomesmentioning
confidence: 99%
“…We used a global measure of job satisfaction because a number of work characteristics have been thought to be related to affective reactions at work. Most work design theory hypothesizes a relationship between work design and job satisfaction and measures job satisfaction using a global measure (e.g., Campion, 1988;Campion & Thayer, 1985;Hackman & Oldham, 1975, 1980. Second, we measured training requirements by using the job zone measure from the O*NET database.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…JD-R studies have demonstrated how the good health of an employee facilitates performance at the organisational level as employees who create their own resources are better able to deal with their job demands and to achieve their work goals Hakanen, 2009;Salanova, Agut & Peiro, 2005;Salanova & Schaufeli, 2008). Similarly, job design research has found evidence for the relationship between job characteristics, such as those outlined in the above propositions, and organisational outcomes such as worker compensation (Morgeson & Humphrey, 2006), training demands (Campion, 1988), skill requirements (Capelli & Rogovsky, 1994) and organisational performance (Ketchen et al, 1997). Lean manufacturing has also been repeatedly associated with improved organisational performance and competitive advantage (Brown et al, 2006;Cua et al, 2001;Fullerton & Wempe, 2009).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…First, physical demands, work conditions, and ergonomics reflect the extent to which the job is designed in terms of biological concerns (Campion & Thayer, 1985). If physical demands increase and work conditions or ergonomics decrease, job incumbents will become increasingly physically uncomfortable (Campion, 1988), which in turn will hurt attitudinal outcomes such as job satisfaction. Moreover, if jobs are uncomfortable and dissatisfying, it is likely that job incumbents will want to avoid going to work and will instead look for new jobs.…”
mentioning
confidence: 99%